Enhancing Pupils’ Academic Performance in Mathematics using Brainstorming Instructional Strategy - K. E. Obafemi (ASEAN Journal of Science and Engineering Education, 2024)
This study investigated the effect of brainstorming instructional strategy on pupils' academic performance in mathematics in Ilorin West Local Government Area of Kwara State, Nigeria. Pretest posttest control group quasi-experimental research design was adopted. A total of 97 pupils from two private primary schools were involved in the study. Three validated research instruments were used for gathering and these included Mathematics Performance Test (MPT), Guide for Brainstorming Instructional Strategy (GBIS), and Guide for Conventional Method (GCM). MPT was tested for reliability using the test-retest method and the reliability coefficient was 0.78. Two hypotheses were formulated and tested with Analysis of Covariance (ANCOVA) at a 0.05 level of significance. The findings of the study revealed that brainstorming had a significant effect on pupils’ academic performance in mathematics. However, the interaction of treatment and gender did not have any significant effect on the academic performance of pupils in mathematics. Based on the findings, it was concluded that brainstorming instructional strategy improved the academic performance of pupils in mathematics regardless of their gender. Based on the conclusion, it was recommended that primary school teachers should be trained in the use of brainstorming instructional strategies in teaching mathematics.